Le roman sans événements : ’Oreille rouge’ d’Éric Chevillard - Maziarczyk, Anna (Studia Romanica Posnaniensia, 2013)
Even though absurd humour and surreal scenes are at first sight the characteristic elements of Eric Chevillard’s style, it is an oversimplification to consider his novels as mere literary jokes. The appeal of this literature stems from the light and witty manner in which it transforms outdated novelistic conventions, deconstructs classic narrative strategies and refuses to fulfill the reader’s expectations. This article seeks to analyse minimal narration, an unusual mode of writing for Chevillard, in Oreille rouge: just like narrative excess, typical of his other works, it results in dematerialisation of the plot and redefinition of the novelistic structure.